Determination sound speed of metal in aqueous solution via laser induced acoustic wave technique - Duralim, Maisarah (Penerbit UTM Press, 2016)
Laser induced breakdown and shock wave propagation are nonlinear phenomena. The high temperature and high pressure associated with plasma formation offering a lot advantages in industrial and scientific research. However not many realized that the end product of nonlinear effect such as the generation of acoustic wave will also attribute to significant impact. Thus the intention of this study is to materialize the usefulness of such acoustic wave for determination the sound speed of metal element like Pb, Hg and K in aqueous solution. In this attempt a Q-switched Nd:YAG laser was focused to induce optical breakdown and its associated shock wave generation which later follow by the generation of acoustic wave. The phenomenon is observed in conjunction with high speed photography based shadowgraph technique. The experimental results of sound speed for K, Hg and Pb is found in good agreement with the standard value from references. This confirmed that laser induced acoustic wave will be other alternative method for measuring sound speed for metal element in periodic table.